2019
DOI: 10.1002/fam.2758
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermal property of intumescent char produced by flame‐retardant high‐impact polystyrene/expandable graphite/microencapsulated red phosphorus composite

Abstract: Summary This paper is aimed to illustrate the structure and thermal property of intumescent char produced by flame‐retardant polymers containing expandable graphite (EG). For this purpose, high‐impact polystyrene (HIPS) flame retarded by EG individually or in combination with microencapsulated red phosphorus (MRP) was prepared. The results indicate that the intumescent char from HIPS/EG/MRP composite, which contains a small amount of phosphorus element and more oxygen element, is much more compact and continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…The EG swells with exposure to heat due to promotion of gas derived from redox reaction in graphite sheets, and subsequently forms worm‐like char that entangle with each other to construct network. In addition, the phosphates decompose into polyphosphates and fill in gap of graphite sheet to improve thermal stability of network 16,17 . However, more than 20 wt% loading of IFRs is inevitable for PS to achieve self‐extinguishment and anti‐dripping performance.…”
Section: Introductionmentioning
confidence: 99%
“…The EG swells with exposure to heat due to promotion of gas derived from redox reaction in graphite sheets, and subsequently forms worm‐like char that entangle with each other to construct network. In addition, the phosphates decompose into polyphosphates and fill in gap of graphite sheet to improve thermal stability of network 16,17 . However, more than 20 wt% loading of IFRs is inevitable for PS to achieve self‐extinguishment and anti‐dripping performance.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the solution mixing begins with the dispersion of the additives in a polymeric solution followed by a controlled solvent evaporation and a composite film casting [ 52 ]. The organic and inorganic compounds, multi-component formulations, and a range of nanomaterials are used as the additive FRs for different sub-classes of styrenic polymers [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ...…”
Section: Fire Retardation Of Styrenic Polymers With Phosphorous-comentioning
confidence: 99%
“…The fire-retarding performance of the ABS copolymer with different aryl cyclic phosphorous FRs revealed that the phosphonate compounds were more thermally stable and generated higher char yields as opposed to phosphinates [ 99 ]. There is a range of publications dedicated to synergistic formulations, for HIPS and ABS, containing red phosphorous combined with other additives: EG [ 100 , 101 , 102 ], Mg(OH) 2 [ 103 , 104 , 105 ], and melamine polyphosphate [ 106 ].…”
Section: Fire Retardation Of Styrenic Polymers With Phosphorous-comentioning
confidence: 99%
“…When heated, EG expands and generates a voluminous isolative layer, providing ame retardance for the polymeric matrix. [25][26][27][28] In recent years, EG has been widely used in polyurethane, 29,30 PP, 31,32 PE, 33 polystyrene, 34 epoxy resin 35 and other polymer ame retardant materials and has achieved satisfactory results. However, when EG is used alone in polymer ame retardation, the carbon layer containing EG is loose and porous, thus hindering perfect ame retardation performance.…”
Section: Introductionmentioning
confidence: 99%